Determinants of consumer trust in e-commerce - Chia, Chee En; Foo, Yi Cheng (2018)
This study is aimed to investigate the determinants of consumer trust in e-commerce in Malaysia. To specifically examine the in depth of determinants of consumer trust and issues related to the research topic has been discussed. This study is designed to achieve the following objectives: (1) To determine the relationship between brand recognition and consumer trust: (2) To identify the relationship between service quality and consumer trust; (3) To examine the relationship between customer satisfaction and consumer trust; (4) To study on the relationship between security and consumer trust; (5) To study on the relationship between word-of mouth communication and consumer trust; (6) To examine the relationship between consumer trust and loyalty and (7) To determine the relationship between consumer trust and purchase intention. Personal distributed questionnaire method and online questionnaire method were selected as a tool to conduct and collect samples. Target populations are Malaysian individuals whom have purchased online recently of age 18 and above. In addition, Partial Least Square (PLS) Path Modeling was used to generate the data and to conduct tests inclusive of reliability, validity and discriminant validity. Throughout the research, the results have shown that variables such as brand recognition, service quality, security, word-of-mouth communication, consumer trust, loyalty and purchase intention have significant relationships with one another. Customer satisfaction shows no significance in the results. To conclude this research, the summary of descriptive analysis, discussion of major findings, implication of the study and the limitation of the study will be discussed in this research study. There are also has several recommendations highlighted to overcome and potential improvement area for future study.